Equitably mirroring the nation: Black students’ experiences in landscape architecture - Belk, Ayana Marie (Kansas State University, 2022)
Black landscape architecture students are the most underrepresented race in landscape architecture programs (Pritchard and Martinez Gonzalez 2020, US Census Bureau 2019). Diversity in the profession begins with increasing the differences in race, gender, and social status of landscape architecture students. Equitably increasing diversity in the profession requires a commitment to actions focused on promoting justice and fairness within the procedures and distribution of resources by landscape architecture institutions (Extension Foundation 2021, 1). Landscape architecture professional organizations have the goal of diversifying the profession to correlate with the 2012 population-share estimates by 2025 “while working toward the longer-term goal of parity with 2060 population projections for the nation as a whole” because they want the profession to better represent the communities they serve (American Society of Landscape Architects, 2018). Without taking an equitable approach to reaching this diversity goal the professional organizations will be mimicking the United States› population demographics without addressing the root causes of outcome disparities within our profession. Understanding Black landscape architecture students’ backgrounds and experiences is key to equitably diversifying the landscape architecture profession. This critical narrative case study (Harper et al., 2016; Solorzano et al., 2000), grounded in Critical Race Theory (CRT), analyzes Black landscape architecture students’ backgrounds and the factors influencing their experiences in discovering, choosing, and navigating the profession and its academic programs. This study addresses: What are Black students’ experiences in discovering landscape architecture as a profession and navigating landscape architecture in academic institutions? Who are Black landscape architecture students? What factors contribute to a successful academic journey for a Black landscape architecture student? What factors make the journey difficult? What do Black landscape architecture students feel would make their journeys more successful? After 47% of current Black landscape architecture students completed the online descriptive data survey, eight students were selected for in-depth one-on-one interviews based on factors such as gender, first-generation status, and their landscape architecture experience thus far. The eight students discussed their experience in discovering, choosing, and navigating their landscape architecture programs. Survey and interview data was coded and analyzed for barriers to equity and supports and then synthesized into barriers, supports, and recommendations represented in graphics and Typographic Narratives. Survey participants were given the option of their name, university, and anticipated graduation date being added to a database of current Black landscape architecture students. The study provides previously unavailable descriptive data on Black landscape architecture students, allowing insights into their discovery and selection of landscape architecture as an academic path. Understanding of their academic experience is gained through students’ descriptions of their academic journey. The barriers, supports, and recommendations identified can inform action towards making landscape architecture an equitably diverse profession and program of study.
Keywords: Landscape architecture; Black students; Diversity; Equity; Institutionalized racism; Higher education